Water Resources in Arid Areas. - Abdalla, Osman (Springer Water., 2017)
This book presents the most recent innovations, trends, concerns and practical challenges, and solutions in the field of water resources for arid areas. It gathers outstanding contributions presented at the International Water Conference on Water Resources in Arid Areas (IWC 2016), which was held in Muscat, Oman in March 2016. The individual papers discuss challenges and solutions to alleviate water resource scarcity in arid areas, including water resources management, the introduction of modern irrigation systems, natural groundwater recharge, construction of dams for artificial recharge, use of treated wastewater, and desalination technologies. As such, the book provides a platform for the exchange of recent advances in water resources science and research, which are essential to improving the critical water situation.